Direct seeding of Brosimum alicastrum Sw. (Moraceae) and Enterolobium cyclocarpum (Jacq.) Griseb. (Mimosaceae) in different habitats in the dry tropics of central Veracruz - Laborde, Javier; Corrales-Ferrayola, Isabel (Instituto de Ecología, A.C., 2012)
Secondary forest in the seasonal tropics is usually dominated by a few pioneer tree species (usually wind-dispersed), while animal-dispersed species with large seeds may be absent. Several studies have shown that directly seeding these tree species in abandoned pastures can be successful; however, information is lacking about the optimal habitat conditions for sowing. We selected two large-seeded zoochorous canopy tree species that are common in the semi-deciduous tropical forest of central Veracruz, Mexico: Brosimum alicastrum and Enterolobium cyclocarpum. Their seeds were sown in seven habitats: six forming a gradient of increasing vegetation structure, from active pasture to 10-year-old secondary forest, and an old-growth forest. We assessed seed predation by granivores, protecting half of the seeds in wire cages. For a year we monitored seedling emergence, survival and growth, re-visiting the sites four-and-a-half years later. Seedling emergence was relatively high (75% in Brosimum, 60% in Enterolobium) and fairly even among habitats. Surprisingly, no seeds were removed by granivores. Enterolobium seedling survival and growth was higher in open habitats (around 60% survival up to a year) than in habitats shaded by woody plants (<10%). For Brosimum, the reverse was true; its seedlings survived and grew better under a dense woody canopy (>80% survival) than in open sites (0%). Our results show that abandoned pastures and secondary forests can be successfully enriched by directly seeding poorly-dispersed forest canopy tree species, if the right habitat for sowing is chosen with care and based on the ecology of seedling establishment of the desired species.